Gas chromatography–mass spectrometry determination of the migration of phthalate plasticisers from polyvinyl chloride in food aliments - BOUSSOUM, M. O.; BELHANECHE-BEMSEMERA, N. (Science des matériaux (Laboratoire LARHYSS); Vol. 8 No 01 (2017): Science des matériaux (Laboratoire LARHYSS) Moi de Janvier, 2017)
In this study, the specific migration of epoxidized sunflower oil (ESO) and di-octyl phthalate (DOP) was addressed by using gas chromatography coupled with mass spectrometry. The test conditions were 12 days. Twelve circular samples of plasticized PVC were immersed in 120 ml of olive oil and aqueous ethanol. A circular sample and 10 ml of food simulant were taken off every day to be analyzed. The rate of mass variation was followed. We first searched for the optimum operating conditions for the analysis of additives in question (ESO and DOP) in based on the measurement of retention time to increase the sensitivity and specificity of the chromatographic system chosen. Keywords: plasticized PVC, migration, DOP, ESO, CG/SM.